2019
DOI: 10.1007/s42452-019-1152-6
|View full text |Cite
|
Sign up to set email alerts
|

Wear and breakage of coated carbide tool in milling of H13 steel and SKD11 hardened steel

Abstract: In the present paper, the wear and breakage mechanisms of coated carbide tools are investigated in milling of H13 steel (HRC 30-35) and SKD11 hardened steel (HRC 58-62). The experiment results indicate that the hardness of workpiece has a dominant effect on tool failure patterns. Due to the low hardness of H13 steel, low-stress-repeated impact load on the tool induces the generation of cracks, but not enough to cause tool fracture. Thus, tool failure pattern is flank wear in milling of H13 steel. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Yan L [21] proved that the tool breakage failure also accounted for a large proportion in the actual milling process, and the tensile stress exceeding the tool tensile strength was the fundamental factor that leads to the tool damage. Gong F [22] studied the fracture mechanism of cemented carbide tool by milling hardened steel, which further proved that the hardness of the workpiece had an effect on the tool failure, and the geometric model of tool wear and the fracture was established. Yuan Q [23] studied that when cemented carbide tools milling workpiece using large cutting parameters, the main form of tool failure was impact damage, and tool wear also lead to tool damage after a period of stable cutting.…”
Section: Introductionmentioning
confidence: 97%
“…Yan L [21] proved that the tool breakage failure also accounted for a large proportion in the actual milling process, and the tensile stress exceeding the tool tensile strength was the fundamental factor that leads to the tool damage. Gong F [22] studied the fracture mechanism of cemented carbide tool by milling hardened steel, which further proved that the hardness of the workpiece had an effect on the tool failure, and the geometric model of tool wear and the fracture was established. Yuan Q [23] studied that when cemented carbide tools milling workpiece using large cutting parameters, the main form of tool failure was impact damage, and tool wear also lead to tool damage after a period of stable cutting.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, experiments revealed that using cutting tools with a smaller rake angle, a smaller right clearance angle, and a large helix angle effectively reduced cutting forces, extended tool life, and facilitated smoother cutting processes. Gong et al [13] conducted milling experiments on H13 steel and SKD11 hardened steel by using coated carbide tools to investigate the tool wear and breakage mechanisms. The results indicated that the hardness of the workpiece had a dominant effect on tool failure patterns.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Inkhamnoi and Jirapattarasilp 26 examined the effects of milling parameters and cooling conditions on the surface hardness of SKD11. Gong et al 27 focused on the breakage and wear mechanisms of coated-carbide tools in the milling process of SKD11. Recently, Dong et al 28 and Duc et al 29 have explored the performance of MQL with MoS 2 /alumina nanoparticles in the milling of SKD11.…”
Section: Introductionmentioning
confidence: 99%